Síntese e caracterização de um novo adsorvente a base de sílica-epóxi-quitosana para remoção de Hg(II) em meio aquoso - Andrade Júnior, Marcos Antonio Santana (2012)
In this study, we evaluated the interaction of the divalent metal ion, Hg (II), with a new adsorbent material formed from three polymers, silica, epoxy resin and chitosan. This material was characterized by CHN elemental analysis, vibrational spectroscopy in the infrared, Raman spectroscopy, nuclear magnetic resonance, thermogravimetric analysis, diffuse reflectance in the UV / Vis. The characterization techniques confirm the formation of hybrid between the three polymers which give the connections from ring opening of the epoxy resin with amino groups by aminopropylated and chitosan. The vibrational spectroscopy helped to elucidate supposed modes of interaction between the Hg (II) and the primary and secondary amines and the oxygen functional groups present in the material. The material has pHpcz = 7.62. The adsorption experiments were carried out using a dosage of 10 g.L-1. The optimum pH for the removal of Hg (II) is equal to 8.0 with a percentage removal of Hg (II) equal to 98%. Kinetic studies of adsorption of Hg (II)- GMP-Sil Chit were performed at initial concentrations of Hg (II) of 3,3x10-5, 6,2x10-4, 1,5x10-3, 4,72x10-3, 6,76x10-3 e 1,66x10-2 mol.L-1 at temperatures of 30, 35, 40 and 45 ° C with equilibrium between 50 and 120 min. The fractional kinetic model was the best fit the experimental data, where kf increased with increasing temperature and nf behaved in a diversified way. Chemical analysis of heat can be obtained adsorption energies and enthalpies of interaction processes. The fractional kinetic model also fit the kinetic isotherms of energy release. The relationship between kf versus C0 enabled revealed the kinetic constant of adsorption and desorption allowing the calculation of the equilibrium constant for the temperatures of 30 and 45 ° C. The values of ΔG < 0, ΔH < 0e ΔS > 0, obtained for the interaction of Hg (II) adsorbent, defined as the process is exergonic, exothermic and spontaneous. The spontaneity of the adsorption process suggests that the new material is promising for the removal of Hg (II) in aqueous solutions.